Epidemiological Trends in the Form of Childhood Tuberculosis in a Referral Tuberculosis Hospital in Shandong, China. (10th August 2020) - Wang, Mao-Shui; Wang, Jun-Li; Liu, Xin-Jie
Abstract : Background. In China, the prevalence of tuberculosis (TB) diseases and epidemiological trends in the TB forms among children are still unclear; a retrospective study was conducted aiming to assess it. Methods. Between January 2007 and September 2020, 1577 consecutive childhood TB patients (aged ≤ 15 years) were included in the study. Data, including demographic information and underlying diseases, were collected from medical records. Then, patients were categorized and reported according to the anatomical site of TB disease. To analyze the epidemiological trends in the proportion of each form of TB disease, a linear-by-linear association was used, and a P value of <0.05 was considered to indicate that a significant change had occurred in the proportion of TB disease over the studied period. Results. During the fourteen-year study period, a total of 1577 children patients were enrolled, including 954 boys (60.5%) and 623 girls (39.5%), with a mean age of 9.26 ± 5.18 years. Among the studied patients, 810 (51.4%) patients have pulmonary TB, 1137 (72.1%) have extrapulmonary TB, 372 (23.6%) have both conditions, and another 765 (48.5%) extrapulmonary cases presented in isolated form. Pleural TB (29.0%) and tuberculous lymphadenitis (23.7%) were the most frequent two forms of childhood TB. In addition, during the past decade, the proportions of pulmonary TB, pleural TB, and tuberculous lymphadenitis showed an increasing trend (all P < 0.05 ). However, no significant trends in the proportions of other forms of TB disease, such as extrapulmonary TB (P > 0.05 ), tuberculous meningitis (P > 0.05 ), endobronchial TB (P > 0.05 ), and disseminated TB (P > 0.05 ), were found. Conclusion. Our findings suggest that childhood TB is facing new challenges, and the policy should be adjusted timely to fit the real situation.